2022
DOI: 10.3389/fneur.2022.830784
|View full text |Cite
|
Sign up to set email alerts
|

Insight Into Regulatory T Cells in Sepsis-Associated Encephalopathy

Abstract: Sepsis-associated encephalopathy (SAE) is a diffuse central nervous system (CNS) dysfunction during sepsis, and is associated with increased mortality and poor outcomes in septic patients. Despite the high incidence and clinical relevance, the exact mechanisms driving SAE pathogenesis are not yet fully understood, and no specific therapeutic strategies are available. Regulatory T cells (Tregs) have a role in SAE pathogenesis, thought to be related with alleviation of sepsis-induced hyper-inflammation and immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 127 publications
(228 reference statements)
0
1
0
Order By: Relevance
“…Although Treg cells can contribute to immune suppression in sepsis, Treg depletion in the murine models of sepsis does not improve mortality rates. In fact, the findings of one study in mice deficient in Treg cells showed that animals could not fight the initial sepsis infection [60]. Therefore, it is clear that a subtle balance of Treg cells is required to maintain immune homeostasis in sepsis.…”
Section: Cd4 + Th Cellmentioning
confidence: 99%
“…Although Treg cells can contribute to immune suppression in sepsis, Treg depletion in the murine models of sepsis does not improve mortality rates. In fact, the findings of one study in mice deficient in Treg cells showed that animals could not fight the initial sepsis infection [60]. Therefore, it is clear that a subtle balance of Treg cells is required to maintain immune homeostasis in sepsis.…”
Section: Cd4 + Th Cellmentioning
confidence: 99%